Pengaruh Model Pembelajaran Self Organized Learning Environment (SOLE) Berbantuan Media Video Animasi terhadap Hasil Belajar IPA Kelas V SD Inpres Pattallassang - Nur Afifah; Irmawanty Irmawanty; Anisa Anisa (Journal on Education, 2024)
The aim of this research is to determine the influence of the Self Organized Learning Environment (SOLE) Learning Model Assisted by Animation Video Media on the Science Learning Outcomes of Class V at SD Inpres Pattallassang. This research is a type of quasi-experimental research with a research design using a nonequivalent control group design using a quantitative approach. The population in this study were all class V students at SD Inpres Pattallassang. The sample in this study was 50 students, the sampling technique used was random sampling technique with the VC class as the experimental class and the VD class as the control class. The independent variable in this research is the SOLE learning model assisted by animated video media, while the dependent variable is the science learning outcomes for class V at SD Inpres Pattallassang. The data collection techniques used were written tests and documentation. The instruments used were observation sheets and science learning outcomes tests. The data collection technique used is a written test in the form of multiple choice questions and documentation. The data analysis techniques used are descriptive analysis of the N-Gain test, inferential statistical tests used prerequisite tests and hypothesis tests. The increase in the experimental class was higher than the control class with the average in the experimental class increasing to 78.40 while in the control class it was 68.60.